Devil’s Thorn (Emex spinosa (L.) Campd.) Response to Tribenuron-methyl and 2,4-D in Ouazzane Region of Morocco - B., Hajjaj; A., El Oualkadi; H., Tantaoui; M., Chentouf (European Scientific Journal, ESJ, 2019)
A soft wheat weed control trial was conducted during the 2016-2017 growing season. The aim of this study is to investigate the effect of two postemergence herbicides Tribenuron-methyl and 2,4 D on Emex spinosa infestation in a soft wheat crop. Treatments consist on two Tribenuron-methyl rates of application and two 2,4-D rates of application. The experimental design was a random block with tree repetitions and observations were made 60 days after application of herbicides. Results showed that treatment with Tribenuron-methyl at 9.50g/ha and 14.25g/ha widely decrease E. spinosa infestations. Tribenuron-methyl at 9.50g/ha recorded 87.8%, 86.1% and 90.5% respectively on E. spinosa density reduction, E. spinosa height reduction, and E. spinosa dry biomass reduction. Tribenuron-methyl at 14.25g/ha recorded 96.3%, 95.5% and 98.7% respectively on E. spinosa density reduction, E. spinosa height reduction, and E. spinosa dry biomass reduction. 2,4 D at 400g/ha and 600g/ha recorded the lowest efficacies that did not exceed 75.2% in all observed parameters.